2002
DOI: 10.1021/la011696s
|View full text |Cite
|
Sign up to set email alerts
|

Significance of the Acidity of Wood to the Surface Free Energy Components of Different Wood Species

Abstract: The surface free energy of several selected wood species was calculated from contact angle measurements according to the Lifschitz-van der Waals/acid-base theory and compared to pH and water-insoluble acid content (i.e., classical acidity). Distinct relationships with increasing statistical significance were found between pH and the Lewis base component and, most clearly, the Lewis acid component. Similar relationships, although less distinct, were observed with the water-insoluble acidity of the examined wood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
21
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 34 publications
7
21
0
Order By: Relevance
“…The results obtained for the surface free energy of eucalyptus wood according to the Owens-Wendt model are presented in table 5. The values obtained for the total surface free energy were comparable with those obtained for other hardwoods [6,7]. On the other hand, it was higher for the loose side of the veneers than for the tight side, which is in accordance with the lower contact angles obtained for the former in the wetting study of eucalyptus veneers with tannin solutions.…”
Section: Confocal Laser Scanning Microscopy (Clsm)supporting
confidence: 87%
See 1 more Smart Citation
“…The results obtained for the surface free energy of eucalyptus wood according to the Owens-Wendt model are presented in table 5. The values obtained for the total surface free energy were comparable with those obtained for other hardwoods [6,7]. On the other hand, it was higher for the loose side of the veneers than for the tight side, which is in accordance with the lower contact angles obtained for the former in the wetting study of eucalyptus veneers with tannin solutions.…”
Section: Confocal Laser Scanning Microscopy (Clsm)supporting
confidence: 87%
“…On the other hand, it was higher for the loose side of the veneers than for the tight side, which is in accordance with the lower contact angles obtained for the former in the wetting study of eucalyptus veneers with tannin solutions. In both cases, although more significantly for the tight side, the dispersive component was higher than the polar one which is habitual in most polymers [6]. These differences in the surface free energy between both sides of the veneers indicated that the rotary-peeling process might have altered wood surfaces in different way influencing wettability.…”
Section: Confocal Laser Scanning Microscopy (Clsm)mentioning
confidence: 86%
“…For all of the wood investigated (except the rotary wood), the total surface free energy ranged from 60 mJ/m 2 to 70 mJ/m 2 , which was higher than the data given in the literature; many authors have found that the surface free energy of wood ranges from 40 mJ/m 2 to 60 mJ/m 2 (Gardner 1996;Gindl and Tschegg 2002;Little et al 2013). This may be caused by two reasons: the acquired method of contact angle used to calculate the surface free energy and differences in used reference liquids.…”
Section: Surface Energy Componentsmentioning
confidence: 68%
“…Also the chemical characteristics of wood surfaces and wood fi bres may vary depending on species and treatment (de Meijer et al 2000 ;Gindl and Tschegg 2002 ;Peterlin et al 2010 ). Thus a method is needed, which is independent of the infl uence of these additional parameters.…”
Section: Introductionmentioning
confidence: 99%